Validation of ICD-10 codes used to identify the main reason for hospitalization due to hyponatremia in Sweden - Cecilia Bergh Fahlén; Issa Issa; Fredrik Sahlander; Jonatan D. Lindh; Jan Calissendorff; Henrik Falhammar; Jakob Skov; Buster Mannheimer (PLoS ONE, 2025)
Purpose Hyponatremia is the most common electrolyte disorder, with potentially serious consequences. Studies validating hyponatremia used as a principal diagnosis are lacking. Studying principal diagnoses is important since it indicates the main reason for inpatient care. The aim of this study was to assess the validity of principal diagnoses of hyponatremia according to the International Classification of Diseases, tenth revision (ICD-10) in patients discharged from hospital. Methods Three independent reviewers retrospectively analyzed medical records of 428 hospitalized patients, ≥18 years old, discharged with a principal diagnosis of either hyponatremia or syndrome of inappropriate anti-diuretic hormone secretion (SIADH) from three different hospitals during 2014–2017. The positive predictive value of hyponatremia as a principal diagnosis was calculated. Results The median age of the studied population was 73 (IQR 64–81) years and 69% were women. The range of sodium levels was < 100 to 139 mmol/L. The mean sodium level was 119 mmol/L. Of the patients 27% were treated in an intensive care unit (ICU)/high dependency unit (HDU). Hyponatremia was deemed to be the principal cause of inpatient care in 411 out of 428 patients, corresponding to a positive predictive value for hyponatremia as a principal diagnosis of 96% (CI 95% 94–98). Conclusions The current study showed that 19 diagnoses out of 20 were correct implying a high validity. Thus, a principal diagnosis of hyponatremia, appears to be a useful measure in clinical and epidemiological studies aiming to target a clinically relevant consequence of hyponatremia in hospitalized patients.